CASES OF DISSEMINATED AND GIANT JUVENILE XANTHOGRANULOMA IN CHILDREN - E. I. Pil'gui; Yu. V. Rovenskaya; A. K. Gevorkyan; L. K. Aslamazyan; G. V. Ermilova; G. V. Men'shchikova (Педиатрическая фармакология)
Juvenile xanthogranuloma is the most common clinical variant of the class II histiocytosis. This article presents two clinical observationsof papulonodular juvenile xanthogranuloma, specification of epidemiological data, clinical and histological peculiarities of the disease. Due to difficulty diagnosing and low incidence of this form of the disease, specific attention is given to the issues of differential diagnosis; the article also present an algorithm for examining patients with suspected juvenile xanthogranuloma in order to rule out a systemic process.